Inheritance and combining ability of grain yield in half diallel barley population - Patial, Madhu; Pal, Dharam; Kapoor, Ritika; Pramanick, K K (Journal of Cereal Research, 2018)
Studies on the genetic control of grain yield are of great importance for devising effective breeding programmes for yield gain in barley. Hence, inheritance of grain yield, heterosis and combining ability was investigated in barley population obtained from half-diallel crossing among 7 parental lines. The analysis of variance revealed that mean squares due to genotypes were highly significant for grain yield indicating wide diversity among the parental materials used in the study. Mean squares of general combining ability (GCA) and specific combining ability (SCA), the ratio of GCA to SCA mean squares and portion of additive and dominance variances showed, the importance of both additive and non-additive gene effects for grain yield. The non-significant ratio of GCA to SCA mean square highlighted that non-additive gene effects were more important than additive effects. Distribution of dominant and recessive alleles in parents was asymmetrical and parents possess the majority of recessive alleles. Since an average degree of dominance has values greater than 1, which indicated the over-dominance type of gene action in the inheritance of the grain yield. The parent BHS400 was considered suitable according to its yield capacities and general combining ability effects. Only 2 crosses viz., BHS400 X RD2660 and BHS400 X RD2552 had significantly higher grain yield than that of the check variety (BHS400), high significant SCA values and high significant useful heterosis values. Considering average narrow-sense heritability and over-dominant effects in the geneticÂ control of grain yield it is better to postpone selection for this trait until advanced breeding generations. Â Doi.org/ 10.25174/2249-4065/2018/83278